Efektivitas Music Therapy dalam Mengatasi Stres pada Remaja - Iswandi, Firenia Aprilaniki; Hamama, Dian; Fanesha, Rizkiqa Tria; Aulia, Prima (AHKAM, 2024)
Stress is a common experience among individuals, including adolescents who face academic, social, and emotional pressures. Excessive stress negatively impacts their physical and mental well-being as well as academic performance. Music therapy has been recognized as a potential intervention to reduce stress. This experimental study used a one-group pretest-posttest design. The subjects were 9 adolescents aged 15-18 years from West Sumatra who were experiencing stress. The intervention involved four sessions of music therapy over a period of time. Stress levels were measured using the modified Perceived Stress Scale (PSS-10) before and after the intervention. Data were analyzed using the Paired Sample T-test. The results indicated a significant reduction in stress levels among 8 out of 9 subjects after the music therapy intervention, with a p-value of 0.002, indicating a significant difference between pre-test and post-test scores. Music therapy is effective in significantly reducing stress levels in adolescents. The findings support the use of music therapy as a beneficial intervention for managing stress in this age group.